The Efficacy of Peloidotherapy on Knee Osteoarthritis - Ufuk Şen; M. Zeki Karagülle; Mine Karagülle (Archives of Rheumatology, 2007)
Objective: This study was designed to evaluate the efficacy of peloid application(mud pack therapy) in patients with knee osteoarthritis. Patients and Methods: In this study, we included 20 patients with diagnosed as having osteoarthritis of the knee according to the American College of Rheumatology (ACR). The mean age was 56.95 (45-67) years;15 females and 5 males. The osteoarthritis of the knees were bilateral in all patients. The Mud pack orginated from Sarayköy, Denizli. The Mud pack was applied at 45ºC for 30 minutes and continued once a day for 12 days. All patients were evaluated using VAS, WOMAC and SF-36 scores. Results: All parameters were administered three times (at the baseline, the end of the treatment and the end of the third month). With regard to our results, an excellent improvement was observed in terms of VAS, WOMAC and physical function, limitation of physical role, pain, general health, vitality and mental health of SF-36 scores (p<0.0001), while a medium improvement was seen in terms of social function and emotional role of SF-36 scores (p<0.05). Conclusion: We conclude that mud pack therapy gives satisfatory results in the early period for patients with knee osteoarthritis and that is a time and quality of life saving procedure, which can be safely applied for the elderly patients. (Rheumatism 2007; 22: 55-9)